2021
DOI: 10.3390/s21144866
|View full text |Cite
|
Sign up to set email alerts
|

Surface Wettability Tuning of Acrylic Resin Photoresist and Its Aging Performance

Abstract: Photoresist is the key material in the fabrication of micropatterns or microstructures. Tuning the surface wettability of photoresist film is a critical consideration in its application of microfluidics. In this work, the surface wettability tuning of acrylic resin photoresist by oxygen plasma or ultra-violet/ozone, and its aging performance in different atmospheres, were systematically studied. The chemical and physical characterizations of the surfaces before and after modification show a dramatic decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In Figure 2a, the peaks located at 1757 and 1249 cm −1 are assigned to C�O and C−O−C stretching vibrations of ester groups of PMMA, respectively. 43,52 After UV/Ozone treatment, the intensity of these two peaks noticeably decreases; meanwhile, higher intensities are observed at the peak shoulders in the ranges of 1000−1125 and 1600−1800 cm −1 , suggesting the photolysis of ester groups yields oxygen-containing polar groups such as carboxylic acids, aldehydes, ketones, and alcohols. 43 The appearance of the peak at 3000−3600 cm −1 , which is attributed to OH stretching, also indicates the generation of hydroxyl groups after UV/Ozone treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 2a, the peaks located at 1757 and 1249 cm −1 are assigned to C�O and C−O−C stretching vibrations of ester groups of PMMA, respectively. 43,52 After UV/Ozone treatment, the intensity of these two peaks noticeably decreases; meanwhile, higher intensities are observed at the peak shoulders in the ranges of 1000−1125 and 1600−1800 cm −1 , suggesting the photolysis of ester groups yields oxygen-containing polar groups such as carboxylic acids, aldehydes, ketones, and alcohols. 43 The appearance of the peak at 3000−3600 cm −1 , which is attributed to OH stretching, also indicates the generation of hydroxyl groups after UV/Ozone treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely reported that plastics conventionally treated by plasma and UV/Ozone will experience hydrophobic recovery with time, i.e., their WCA increases back to the value before the treatment. ,,, It has been proposed that airborne hydrocarbon can adsorb on plastic surface and thus lowers the surface energy and increases the WCA . Aging tests were conducted on our Zdol-coated and UV/Ozone-treated plastics with simultaneous hydrophilicity/oleophobicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WB samples, after 30h AcA have lower polar component but higher total SFE values. This can be attributed to the acrylic resin that is a common ingredient in water based varnishes and it tends to become more hydrophobic after exposure to UV or ozone (Dou et al, 2021). On the other hand, with the increase of TiO2 nanoparticle weight ratio (%), the wettability of TiO2 coated samples also increases but after the AcA it lowers.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the thicknesses of photoresist produced in 2021 and 2022 as the following, and we found that the one-year storage increases the thickness by about 0.2um on average (Table 3. ), since the photoresist is easily affected by light exposure and high temperature during the storage [8]. Therefore, the expired photoresist must be avoided to achieve the desired experiment results.…”
Section: Testing Results and Analysismentioning
confidence: 99%